Material Residence Time in Marine Canopies Under Wave-Driven Flows - Abdolahpour, Maryam; Ghisalberti, Marco; McMahon, Kathryn; Lavery, Paul (Frontiers in Marine Science, 2020)
Coastal canopies (e.g. seagrasses, coral reefs, and kelp forests) are vitally important ecosystems that provide a range of ecological services (e.g. oxygen production, sediment stabilization and trapping and recycling of nutrients). The long-term health, productivity and survival of these canopies rely heavily on the residence time of ecologically-significant materials in these environments. Recent studies have shown that the presence of submerged canopies induces strong mean current over the canopy top, even in purely wave-dominated environments. Thus, in addition to vertical mixing, the horizontal flushing of materials (resulting from these canopy-induced currents) will dictate rates of water renewal and, therefore, residence time in wave-dominated flows over submerged canopies. Building on this recently-improved understanding, this paper provides (for the first time) a framework for estimation of material residence time (Tres) and its variation with core system parameters, including both canopy and wave characteristics. This is done through consideration of a P'eclet number (Pe) which is the ratio of mixing to advective time scales. Prediction of residence time for a wide and realistic range of marine canopies (i.e. mixing dominated with Pe<<1, advection dominated with Pe>>1, and transitional (Pe O (1)) reveals that while Tres decreases with wave height and increases with water depth, it has a complex relationship with canopy density and height. Importantly, residence time can vary from orders of seconds to hours, depending on wave and canopy properties. This has considerable ecological implications for marine canopies through the direct impact on a range of chemical and biogeochemical processes within the canopy. The framework presented here provides a critical step forward in being able to predict residence time in coastal canopies and test the interacting set of factors that influence the residence time in real, complex systems.